The effect of different degrees of visible trephine-based foraminoplasty in PETD surgery on lumbar biomechanics: a finite element analysis - Li, Duohua; Sun, Wei (Frontiers in Bioengineering and Biotechnology, 2025)
PurposeThis study aimed to evaluate the effect of the degree of facet joint resection under the combined action of large-channel endoscopy and visualized trephines on lumbar biomechanics.MethodsThe original CT data of a healthy male volunteer were selected. An L3-5 lumbar spine model, M0, was established via the three-dimensional finite element method. Different degrees of resection of the superior articular process of L4 were simulated via a visualized trephine during the operation, and six models were established (M1: tip resection; M2: resection of the ventral 1/3; M3: resection of the ventral 1/2; M4: resection of the ventral 2/3; M5: resection of the ventral 3/4; and M6: complete resection). Loads were applied to the model to simulate six motions of flexion, extension, left/right lateral bending, and left/right rotation. The stress distributions of the vertebral body, intervertebral disc and articular cartilage of the L3-4 segment and adjacent segments were observed.ResultsCompared with M0, L4 vertebral stress was elevated in the M1 model, L4 vertebral stress was reduced in the M2 and M3 models, and L4 vertebral stress was significantly elevated in the M4, M5, and M6 models (P < 0.05). Compared with M0, the differences in the L3 vertebral body, L5 vertebral body, L3-4 disc, and L4-5disc stresses were not statistically significant (P > 0.05) in the M1, M2, and M3 models, whereas the stresses were significantly higher (P < 0.05) in the M4, M5, and M6 models. Compared with M0, the difference in L3-4 facet joints stress between the M1, M2 and M3 models was not statistically significant (P > 0.05), whereas the L3-4 facet joints stress between the M4, M5 and M6 models were significantly higher (P < 0.05), with a greater increase on the left facet joint.ConclusionWhen more than half of the superior articular process of L4 is resected under large-channel endoscopy, the stress on the vertebral body, intervertebral disc and articular cartilage of the L3-4 segment increases, which may cause iatrogenic instability but has no significant effect on the stress on the vertebral body or intervertebral disc of adjacent segments.